God-World-Man: Towards an Integral View of Divine Revelation - Kakkanattu, Joy Philp (Asian Horizons, 2011)
Antony Edanad, God-World-Man. Towards an Integral View of Divine Revelation, Bangalore: Dharmaram Publications, 2010. Pages: xvi+175. ISBN: 978-81-89958-38-1